Agile Governance dalam Penanganan Covid-19 di Kota Bekasi Tahun 2021 - Isnaeni Yuliani (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2022)
The Covid-19 pandemic has affected various sectors and spread widely to various countries, including Indonesia. The fluctuating development of Covid-19 in Bekasi City has caused the Bekasi City Government to implement various policies and efforts to handle Covid-19 in Bekasi City so that it does not have a bad impact. Not only that, the synergy of various parties and stakeholders has formed a collaboration in handling Covid-19 in Bekasi City. In this study, researchers analyzed Agile Governance in Handling Covid-19 in Bekasi City in 2021 using agile governance theory. According to Alexandre J. H. de O. Luna, Philippe Kruchten, Marcello L. G. do E. Pedrosa, Humberto R. de Almeida Neto, and Hermano P. de Moura, there are 6 (six) principles of agile governance, namely good enough governance, business driven, human focused, based on quick wins, systematic and adaptive approach and simple design and continuous refinement. The research method used is qualitative research. Data collection techniques used in this study, namely observation, interviews, and documentation. Based on the results of this study, it shows that the application of agile governance in handling Covid- 19 in Bekasi City in 2021, when viewed from the agile governance principles, has achieved very good results. The Bekasi City Government has been alert, fast, and responsive in responding to the Covid-19 pandemic in the Bekasi City area. The Bekasi City Government is also adaptive in implementing various policies in response to unexpected changes.